Islamic jurisprudence on the regulation of armed conflict : text and context - Badawi, Nesrine, (History of Warfare;, 2019)
In Islamic Jurisprudence on the Regulation of Armed Conflict: Text and Context, Nesrine Badawi argues against the existence of a "true" interpretation of the rules regulating armed conflict in Islamic law. In a survey of formative and modern seminal legal works on the subject, the author sheds light on the role played by the sociopolitical context in shaping this branch of jurisprudence and offers a detailed examination of the internal deductive structures of these works.